Coastal Engineering and Geosciences - Dominic Reeve (Reference Module in Earth Systems and Environmental Sciences, 2021)
The aim of this article is to provide an introductory review on coastal engineering, emphasizing beach and shore protection. It is intended as a reference guide to a senior undergraduate or early career researcher who wants to pursue the topic to understand it at more than a superficial level.A brief history of the development of coastal engineering as a discipline is provided before a discussion of the main types of coastal structure. The main physical concepts behind coastal flood defence, coastal protection and coastal harbor works are discussed in the context of the scientific understanding and practical engineering requirements.